Importance of bioconvection flow on tangent hyperbolic nanofluid with entropy minimization - Faizan Ahmed, M.; Khalid, M.; Ali, Farhan; Al-Bossly, Afrah; Alduais, Fuad S.; Eldin, Sayed M.; Saeed, Anwar (Frontiers in Physics, 2023)
The amalgamation of microorganisms in the nanofluid is significant in beautifying the thermal conductivity of several systems, such as microfluid devices, chip-shaped microdevices, enzyme biosensors, and many more. The current investigation studies mixed convective flow of the entropy minimization of unsteady MHD tangent hyperbolic nanoliquid due to a stretching surface having motile density via convective and slip conditions. For the novelty of this work, the variable transport characteristics caused by dynamic viscosity, thermal conductivity, nanoparticle mass permeability, and microbial organisms diffusivity are taken into consideration.It is considered that the vertical sheet is studying the flow. Using the appropriate alteration, the governing equations for the most recent flow analysis were altered into a non-dimension relation. Through the Matlab Software bvp4c, the PDE model equations have been made for these transformed equations. Engineering-relevant quantities against various physical variables include force friction, Nusselt number, Sherwood number, and microorganism profiles.The results showed good consistency as compared to the current literature. Moreover, these outcomes revealed that an augmentation in the magnitude of the Magnetic field and velocity slip parameter declinesthe velocity profile. As the reverseimpact is studied in the . In addition, heat transfer is typically improved by the influence of thermal radiation parameters, Brownian movement, and thermophoretic force. The physical interpretationhas existedthrough graphical and tabular explanations.